9514 1404 393
Answer:
x = 3.6
Step-by-step explanation:
The angle bisector divides the triangle proportionally.
The base segment to the right of the bisector is 6-x, so we can write the proportion ...
x/6 = (6-x)/4
Multiplying by 12, we get ...
2x = 3(6 -x)
5x = 18 . . . . . add 3x
x = 18/5 . . . . divide by 5
x = 3.6
_____
<em>Alternate solution</em>
Since the base of the triangle is given as a left-part and a sum-of-both-parts, we can write the proportion the same way:
left-part / sum-of-both-parts = x/6 = 6/(6+4)
Then the solution is x = 6(6/10) = 36/10 = 3.6.
Doing it this way avoids having x on both sides of the equation, so makes solving the equation be "one step."
Answer:
See attached
Step-by-step explanation:
<em>Refer to attachment</em>
- a. Law of Syllogism
- b. No valid conclusion
- c. Law of Detachment
Answer:
<em>1+√3</em>
Step-by-step explanation:
Area of the triangle = 1/2 * base * height
Area of the triangle = 1/2 * AC * BD
We need to get AC
AC = AD+DC
Get base AD using SOH CAH TOA
tan 45 = 4/AD
AD = 4/tan45
AD = 4/1
AD = 4
Get DC
tan 30 = 4/DC
DC = 4/tan 30
DC = 4/(1/√3)
DC = 4√3
AC = 4 + 4√3
AC = 4(1+√3)
Get the Area of the triangle
<em>Area = 1/2 * 4 * 4(1+√3)</em>
<em>Area of the triangle = 1+√3</em>
Answer:
14491.060542
Step-by-step explanation:
123 centimeters into dekameters
0.123
10 centimeters = 1 decimeter
100 decimeters = 1 dekameter
Therefore, 100 centimeters = 10 decimeters = 0.1
23 centimeters = 2.3 decimeters = 0.023
0.1 + 0.023 = 0.123 dam